Oral microbial dysbiosis in cardiovascular diseases - Osiak, Joanna; Wołowiec, Łukasz; Żukow, Xawery; Fydrych, Dagmara; Jasniak, Albert; Gawłowska, Kinga; Staniewska, Agata; Grześk, Grzegorz (Journal of Education, Health and Sport, 2023)
The most common diseases in humans are oral infections. Although modern research is mainly concerned with the role of the gut microbiota in systemic diseases, there are also reports indicating that oral infections, and especially periodontal infection, are one of the risk factors for atherosclerotic cardiovascular disease (CVD).The composition of the oral biofilm is a community of several hundred species of bacteria, fungi, spirochetes, viruses and protozoa. It varies depending on the state of health and disease. Pathogenic bacteria in the oral cavity can cause systemic disease by entering the bloodstream or by triggering immune responses at the cellular level. The discovery of the role of the oral microbiome in CVD is leading to new methods of prevention and their treatment. In this review, we discuss the various mechanisms by which oral dysbiosis may contribute to the pathogenesis of CVD as well as available options for their prevention and treatment. Oral dysbiosis, or the imbalance of bacteria in the oral cavity, has been linked to an increased risk of CVD. Several mechanisms have been proposed to explain how oral dysbiosis may contribute to CVD, including: The production of inflammatory molecules by oral bacteria. The activation of the immune system, which can lead to inflammation throughout the body. The entry of oral bacteria into the bloodstream, where they can travel to other organs and tissues. There are a number of things that can be done to prevent oral dysbiosis and reduce the risk of CVD, including: Good oral hygiene, such as brushing and flossing twice a day. Regular dental checkups and cleanings. Avoiding tobacco use. Eating a healthy diet. Conclusions. The evidence is growing that oral dysbiosis is a risk factor for CVD. Further research is needed to better understand the mechanisms involved and to develop effective interventions for prevention and treatment. The following are some other important points: The role of oral dysbiosis in CVD is likely to be complex and involve multiple factors. The effects of oral dysbiosis on CVD may vary depending on the individual’s overall health status and other risk factors. More research is needed to determine the optimal methods for preventing and treating oral dysbiosis in order to reduce the risk of CVD.